(untitled) (Tempo e Argumento, 2010)
The virgin forest is a recurrent element in the Brazilian social imaginary. Although the mistake in considering “virgin” the forested areas has already been proved, human action, even indirect, left marks throughout the planet. This essay seeks to understand the reasons for the persistence of the term virgin forest in our imaginary. It is postulated that the expression “virgin forest” is part of a modern myth about nature; it is a “misunderstanding” that belongs to the ethnocentric culture; it is an ideology that justifies the Western domination; it is an appropriated representation and has been reelaborated in different social configurations; it is a long-lasting element that is anchored in the disjunction of nature and culture, which is part of the hegemonic world view in the West.